One-minute Bible stories Old Testament - Lewis, Shari; Matthews, Gerry; Ewing, C. S. (New York Bantam Doubleday Publishing, 1986)
Retells twenty well-known Old Testament stories and parables in a simple, one-minute format, from "Adam and Eve" to "Daniel in the Lion's Den."
"A Yearling book."
8 - 10 years
73200
Keywords: Bible stories, English -- O.T.; Bible stories -- O.T.